The Effect of Corporate Income Tax on Investment in Japan - Reny Andriati; Andriatno Aan (Jurnal Ekonomi Dan Statistik Indonesia, 2022)
The purpose of this research is to analyse and examine the effect of corporate income tax on the investment in Japan from 1987 to 2016. It is an associative-causal research. The secondary data are taken form International Monetary Fund, International Financial Statistics and data files using World Bank. The hypotheses were tested by using the multiple linear regression analysis. The results of this research showed that, simultaneously, corporate income tax rate and interest rate have highly significant effect on investment. After the research is conducted and it was analysed with partial test, corporate income tax rate negatively affects investment in Japan. It is highly recommended that Japan government should reduce the corporate income tax on companies so that there will be more investment in Japan. JEL Classification: E22, H32